Impact of Subjective Norms on Assertive Impression Management Motivation/ 主观规范对获得型I印象管埋动机的影响机制研究 - Zhao, Bin; Han, Y.; Liu, Yan Quan (Software Science, 2020)
Keywords: dept.ils; ⛔ No DOI found

Information Accessibility, How Far Is It?——An Empirical Research of 146 US Urban Public Libraries / 信息无障碍,距离还有多远?——对146家美国城市公共图书馆的调查 - Guo, Y.; Xi, J.; Liu, Yan Quan (图书馆论坛 [Sun Yat-Sen Library of Guangdong Province], 2020)
文章以美国城市公共图书馆协会146家图书馆为调查对象,借助无障碍评估工具WAVE对这些馆网站主页进行测评,逐一开展网站访查和内容分析,统计为残障用户提供服务的情况。调查发现,美国城市公共图书馆网站达到Section 508信息无障碍标准的比例只有15%,“缺少表单标签”“链接图像缺少替代文本”等是常现错误;55%图书馆网站主页有残障用户服务信息。我国公共图书馆应重视信息无障碍建设,遵循信息无障碍标准,定期进行审查与维护,借助信息无障碍技术提供残障服务。
Keywords: dept.ils; ⛔ No DOI found; 信息无障碍; 公共图书馆; 残障用户; 美国; 调查

Are Ivy League libraries’ websites ADA compliant? - Yang, Wenfan; Zhao, Bin; Liu, Yan Quan; Bielefield, Arlene (Information Technology and Libraries, 2020)
As a doorway for users seeking information, library websites should be accessible to all, including those who are visually or physically impaired and those with reading or learning disabilities. In conjunction with an earlier study, this paper presents a comparative evaluation of Ivy League university library homepages with regard to the Americans with Disabilities Act (ADA) mandates. Data results from WAVE and AChecker evaluations indicate that although the error of Missing Form Labels still occurs in these websites, other known accessibility errors and issues have been significantly improved from five years ago.
3 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

The provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic - Guo, Yajun; Yang, Zinan; Yang, Zhishun; Liu, Yan Quan; Bielefield, Arlene; Tharp, Gregory (Library Hi Tech, 2020)
Purpose: The purpose of this paper is to identify the measures employed in the provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic, noting the challenges and issues inherent in providing substantial services while undergoing a public health emergency. Design/methodology/approach: This paper uses an analytical survey study of 137 Chinese academic libraries using data collected through a combination of website investigation, social media access and direct correspondences. Findings: Over 94% of Chinese academic libraries released COVID-19-related information through their websites; the majority switched their service focus to partly or solely remotely online, including remote access, free electronic resources, virtual references reachable 24/7 and research support services deliverable online; services of print materials were altered to e-books for conveniences. Research limitations/implications: It should be noted that the survey was conducted from February 12 to April 5, 2020; because of the rapid updates to the library's website and social media channels, the status of their patron services are in the process of dynamic changes and that there should be many libraries that have adopted some patron service methods, but this study is difficult to cover comprehensively. In addition, patron services carried out offline by the surveyed libraries but not disclosed on the online platform could not be analyzed in a way that would be consistent with the data provided by the survey. Originality/value: By providing evidence of the current status of patron services in Chinese academic libraries during the COVID-19 pandemic, this study helps fulfill the scant empirical attention given to the impact of nationwide public health crises on academic libraries and offers new data of the best practices that help library administrators enhance the impact, efficiency and value of library services to their target community users. © 2020, Emerald Publishing Limited.
32 citations (Crossref) [2023-10-31] tex.ids: guoProvisionPatronServices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088570958 type: Article
Keywords: Academic libraries; COVID-19; China; Patron services; Survey; Virtual services; dept.ils; peer-reviewed